Time-resolved electron properties of a HiPIMS argon discharge via incoherent Thomson scattering. (27th March 2019) - Tsikata, Sedina; Vincent, Benjamin; Minea, Tiberiu; Revel, Adrien; Ballage, Charles
Abstract: In recent years, planar magnetrons used for deposition have been increasingly operated in pulsed, high-current regimes. These dense, transient plasmas present a challenge for both simulation and diagnostic measurements. In this communication, a recently-developed incoherent Thomson scattering diagnostic is applied for the first time to time-resolved measurements of electron properties in a high-current pulsed argon discharge. These measurements give access to electron properties throughout the entire pulse duration, from discharge ignition into the afterglow phase. An increase in electron density of two orders of magnitude is observed from ignition to the peak of the current ramp, while the electron temperature exceeds 10 eV almost instantaneously and saturates near 3 eV during the pulse. Diffusion in the afterglow phase is associated with decreases in both the electron density and temperature.